Ordinance No. 51: An Ordinance to Establish a Criminal Code, in THE GLOBE JOURNAL, Jun. 5, 1880, at 2, § 6 - (:unkn) unknown (My University, 1880)
§ 6: It shall be unlawful for any person or persons to maliciously or wilfully disturb the peace by loud or unusual noises, or by tumultuous and officious carriage, or by menacing or threatening, or traducing, or assaulting, or striking, or wounding, or challenging to fight, or fighting another or others, or by quarrelling or rioting, or discharging fire-arms, or by ringing bells or beating upon or otherwise producing loud and disagreeable noises from metalic or other substances...
Keywords: DISCHARGE